"For Such a Time as This": Gender Issues in Twenty-First Century Norwegian and Swedish Pentecostal Churches. (25th July 2016) - Smidsrød, Åse-Miriam
Abstract : Although there has been a shift from a restrictive to a more egalitarian view regarding women in leadership in Norwegian and Swedish Pentecostal churches, new research has shown that relatively few women are actually ministering as pastors and elders. Although there are no pronounced theological obstacles for women as leaders, many Norwegian and Swedish women still view the movements as male dominated. This article traces the recent debate about women in leadership in Norwegian and Swedish Pentecostalism and highlights some of the female voices that have spoken out against the negligence of male leaders to promote women into leadership positions or as speakers in national conferences. The article further reflects on the relationship between gender issues in society and the situation of female leaders in the Pentecostal Movements and concludes by giving a number of suggestions of how to overcome the status quo.